Promoting family wellbeing through parenting support in ECEC services: parents' views on a model implemented in Ireland - Leitão, Catarina; Shumba, Jefrey (Frontiers in Education, 2024)
Introduction Providing support to parents during the children's early years can positively impact children's development and families' wellbeing. An innovative parenting support model within ECEC services, called Powerful Parenting, has been implemented in Ireland. This model involves placing one dedicated Facilitator in each ECEC service to support parents based on their families' needs. The current study aimed to explore parents' views about this model. Methods Twenty-seven parents were interviewed. Content analysis was used to identify the activities in which parents participated. Thematic analysis was used to explore their views on the model or Facilitators' work. Results The activities organised by the Facilitators in which parents participated included one-to-one meetings, group work, and coordination with other services for children and families. Valued aspects included Facilitators showing high interest in their work, being approachable and responsive to parents' needs, and constituting a central point of contact, bridging the home and the ECEC service. Perceived outcomes for parents included a better understanding of their children's needs, facilitated access to services for families, and socio-emotional benefits. Discussion A parenting support model involving a new professional role, that of the Facilitator, in ECEC services can potentiate accessible and tailored support according to families' needs.